2016
DOI: 10.1007/s00441-016-2389-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal-epithelial signalling in tumour microenvironment: role of high-mobility group Box 1

Abstract: Glucose deprivation, hypoxia and acidosis are characteristic features of the central core of most solid tumours. Myofibroblasts are stromal cells present in many such solid tumours, including those of the colon, and are known to be involved in all stages of tumour progression. HMGB1 is a nuclear protein with an important role in nucleosome stabilisation and gene transcription; it is also released from immune cells and is involved in the inflammatory process. We report that the microenvironmental condition of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…This inflammatory response induced by TLR4 and HMGB1, can also promote angiogenesis and metastasis in melanoma models after UV exposure 40 . Various types of tumor-derived cell lines release HMGB1 in different conditions, such as glucose deprivation, leading to increased proliferation, migration and invasion of stromal cells involved in all stages of tumor progression through TLR4 activation 41 . Interestingly, autophagic cancer-associated fibroblasts secrete HMGB1 activating TLR4 in luminal breast cancer cells, enhancing their stemness and tumorigenicity, correlating TLR4 activation with poor prognosis and increased relapse rate 42 .…”
Section: Discussionmentioning
confidence: 99%
“…This inflammatory response induced by TLR4 and HMGB1, can also promote angiogenesis and metastasis in melanoma models after UV exposure 40 . Various types of tumor-derived cell lines release HMGB1 in different conditions, such as glucose deprivation, leading to increased proliferation, migration and invasion of stromal cells involved in all stages of tumor progression through TLR4 activation 41 . Interestingly, autophagic cancer-associated fibroblasts secrete HMGB1 activating TLR4 in luminal breast cancer cells, enhancing their stemness and tumorigenicity, correlating TLR4 activation with poor prognosis and increased relapse rate 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified the proteins in Lewis lung cancer cell TCL using iTRAQ detection. Among the proteins, RACK1, CTNNBL1, Cullin 3, BCLAF1, RPS6, SOD1, HMGB1, ING1 and ERCC3 have been reported to activate cells and inhibit apoptosis, according to protein databases and previous studies (8,9,(15)(16)(17)(18)(19)(20)(21). Among these proteins, only RACK1, CTNNBL1 and Cullin 3 could be detected by western blotting, and the protein expression levels of RACK1 and CTNNBL1 in TCL were higher than the levels of Cullin 3.…”
Section: Discussionmentioning
confidence: 93%
“…Subsequently, the following proteins were selected as targets in the present study: RACK1, CTNNBL1, Cullin 3, BCLAF1, RPS6, SOD1, HMGB1, ING1 and ERCC3. These proteins have been revealed to promote cell proliferation and inhibit apoptosis in numerous protein databases (Panther, http://pantherdb.org/; UniProt, http://www.uniprot.org/; and NCBI Protein, https://www.ncbi.nlm.nih.gov/protein) and in the literature (8,9,(15)(16)(17)(18)(19)(20)(21). In addition, these proteins exist in ≥2 signaling pathways that are associated with cell proliferation or apoptosis, and the value of type II alveolar epithelial cell lysate/Lewis lung cancer cell TCL calculated by iTRAQ was <0.3 for these proteins.…”
Section: Genementioning
confidence: 99%
“…31) Wang et al reported that extensive transcriptional inhibitive activity of triptolide was associated with the induction of phosphorylation and subsequent proteasome-dependent degradation of RNA polymerase II in breast cancer cells. 32) In view of the anti-cancer activity of triptolide with exact underlining mechanisms largely unknown, in the current study, we aimed to explore the association of anti-growth effect of triptolide and HMGB1 that is located in another vital molecular pathway taking part in the tumorigenicity of breast cancer. Consistent with the results from Li et al that triptolide dose-dependently inhibited the viability of both MCF-7 and MDA-MB-231 cells, 8) our studies confirmed the treatment efficacy of triptolide in breast cancer cells based on the inhibition of the cell viability and clonogenic ability in a dose/time dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…16) Moreover, HMGB1 up-regulation was recently proved to act as the link between tumor-associated inflammation and tumorigenesis. 33) Previously, HMGB1 was identified to stably express in nucleus of the quiescent cells. Then, HMGB1 secretion was confirmed as its translocation from the nucleus to the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%